A systematic review on resource allocation in public health. (30th September 2020) - Barbosa, E; Gonçalves, A; Guerra, M; Cruz, C
Abstract: Background: Research in resource allocation is a need arising from State interference by the allocative function, which seeks to promote resource adjustments with the provision of certain goods and public services (Musgrave, 1974; Musgrave & Musgrave, 1980, Longo & Troster, 1993). In this perspective, a research question arises: how has international literature on the field of Business, Management and Accounting been approaching resource allocation in public health? Methods: Systematic Literature Review through the Scopus Database. keywords: "public health" and "resource allocation". The types were Article and Review. Language: English, since it is internationally accepted in scientific articles, and Portuguese, in order to include Brazilian research. Search period: from 1976 to 2017. Areas: "Business, Management and Accounting". The performed analysis technique was qualitative meta-synthesis and by using the MAXQDA Analytics Pro 18 software. Results: The first identified study was in 2000 Sweden, pulished in Health Care Management Science. The most recente in 2017 Brazil, published in Evaluation and Program Planning. Among the countries that presented the largest production, the United States is highlighted (4). Dispersion of publication among reviews was noted. Generally, publications are grouped in four perspectives: adequate allocation, resource management and effective cost; resource allocation for treating specific diseases; resource allocation for decision-making; and health evaluation and the need of informing resource allocation. The prevailing lack of theoretical grounding must be highlighted. Conclusions: Can be inferred that this production is recent, that it does not possess a specific focus or outline, as there is a variety of approaches, most of them being geared towards healthcare and disease control, such as cancer, diabetes, overweight, rabies, malaria and infectious diseases. Key messages: International literature indicates that the theme is yet unexplored in the field of Business, Management e Accounting and most studies are geared towards healthcare and disease control. Allocation in the public-health policy as a function of the role of the State in providing the necessary budget for financial availability and not cost-wise, suggests lack of research.